2018
DOI: 10.1111/jcmm.13823
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of gastric cancer‐associated gene signatures: Evidence based on a meta‐analysis using integrated bioinformatics methods

Abstract: Selecting differentially expressed genes (DEGs) based on integrated bioinformatics analyses has been used in previous studies to explore potential biomarkers in gastric cancer (GC) with microarray and RNA sequencing data. However, the genes obtained may be inaccurate because of noisy data and errors, as well as insufficient clinical sample sizes. Thus, we aimed to find robust and strong DEGs with prognostic value for GC, where the robust rank aggregation method was employed to select significant DEGs from eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In our study, we combined the GDSC, CCLE, and TCGA database to identify six new target genes (FBN1, FN1, HGF, MMP9, THBS1 , and VCAN ). A few of articles reflected that some indexes could affect the proliferation and invasion of GC by regulating HGF or MMP9 ( Appleby et al, 2017 ; Matsumoto et al, 2017 ; Zhang et al, 2017 ; Ding et al, 2018 ; Wang R. et al, 2018 ), but the function of these six genes in GC was still not well-known, especially FBN1, FN1 , and VCAN ( Lee et al, 2016 ; Sakai et al, 2016 ; Wang J. et al, 2018 ; Jiang et al, 2019 ). By observing the relationships between target genes and important factors that have proven to affect the treatment and prognosis of GC, such as immune infiltration, tumor purity, TMB, TME score, and oncogenic signaling pathways, we expect that the six genes could be considered as new prognostic targets in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we combined the GDSC, CCLE, and TCGA database to identify six new target genes (FBN1, FN1, HGF, MMP9, THBS1 , and VCAN ). A few of articles reflected that some indexes could affect the proliferation and invasion of GC by regulating HGF or MMP9 ( Appleby et al, 2017 ; Matsumoto et al, 2017 ; Zhang et al, 2017 ; Ding et al, 2018 ; Wang R. et al, 2018 ), but the function of these six genes in GC was still not well-known, especially FBN1, FN1 , and VCAN ( Lee et al, 2016 ; Sakai et al, 2016 ; Wang J. et al, 2018 ; Jiang et al, 2019 ). By observing the relationships between target genes and important factors that have proven to affect the treatment and prognosis of GC, such as immune infiltration, tumor purity, TMB, TME score, and oncogenic signaling pathways, we expect that the six genes could be considered as new prognostic targets in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted protein acidic and rich in cysteine (SPARC) is regarded as a collagen chaperone because it binds to the procollagens and its existence is essential for collagen deposition in tissues [29,48]. SPARC overexpression has been demonstrated in some cancers, such as pancreatic cancer [49], esophageal squamous cell carcinoma [50], and GC [51]. In contrast, some studies have shown that SPARC expression is reduced in bladder cancer [52] and acute leukemia [53].…”
Section: Discussionmentioning
confidence: 99%
“…Elaborate search results of prognostic signatures in GC were shown in Table 1 and Figure 2 (Chen et al, 2005 ; Motoori et al, 2005 ; Xu et al, 2009 ; Takeno et al, 2010 ; Cho et al, 2011 ; Bauer et al, 2012 ; Kim et al, 2012 ; Wang et al, 2013 , 2017b , 2018 ; Lee et al, 2014 ; Pasini et al, 2014 ; Li et al, 2016 ; Zhao et al, 2016 , 2019 ; Hou et al, 2017 ; Kuang et al, 2017 ; Lafrenie et al, 2017 ; Liu et al, 2018 , 2019 ; Peng et al, 2018 , 2020 ; Smyth et al, 2018 ; Wu et al, 2018 ; Yuzhalin et al, 2018 ; Chang and Lai, 2019 ; Chang et al, 2019 ; Dai et al, 2019 ; Jiang et al, 2019 , 2020 ; Song et al, 2019 ; Bai et al, 2020 ; Guan et al, 2020 ). Briefly, we got 39 literatures in NCBI PubMed Database following the above procedure ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%